Sejarah Manajemen Kelembagaan Madrasah di Indonesia - Anggita Febriany; Mohammad Aquallurrizal; Salwa Sabila Ghassani (Jurnal Bintang Pendidikan Indonesia, 2026)
This article reviews the history and transformation of madrasah management in Indonesia. Emerging in the early twentieth century, madrasahs developed as educational institutions that combined the traditional values of Islamic boarding schools (pesantren) with the organizational structure of modern schools. This study employs a literature review method to examine the evolution of madrasah governance from the colonial era to the reform era. The findings reveal three major stages in the development of madrasah management. The first stage was the early period, during which madrasahs were independently managed by religious leaders and Islamic organizations with limited government involvement. The second stage was the post-independence integration period, characterized by increasing government intervention in curriculum development, institutional regulation, and legal recognition. The third stage was the modernization era, marked by the issuance of the Joint Decree of the Three Ministers in 1975 and the enactment of the National Education System Law of 2003, which strengthened the position of madrasahs within the national education system and placed them on an equal footing with public schools. These developments encouraged madrasahs to adopt Madrasah-Based Management (MBM) as a strategy to improve educational quality, effectiveness, and competitiveness. Overall, the transformation of madrasah management reflects an adaptive process that enables madrasahs to respond to educational reforms and societal changes while maintaining their distinctive Islamic identity and educational mission.